2006
DOI: 10.1063/1.2236295
|View full text |Cite
|
Sign up to set email alerts
|

THz spectroscopic characterization of biomolecule/water systems by compact sensor chips

Abstract: Articles you may be interested inChiral response of single walled carbon nanotube based sensors to adsorption of amino acids: A theoretical model

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…In particular, we show that, by the use of low-permittivity dielectric materials, they can support the propagation of electrical pulses whose spectra reaching 3 THz for a distance as long as 1 mm. As an application of these devices, also we demonstrate the THz spectroscopic characterization of liquid and powder specimens [11][12][13]. In addition, we show that even lower attenuation can be realized in quadrupole mode in threestrip CPS (TSCPS) on low permittivity substrate.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In particular, we show that, by the use of low-permittivity dielectric materials, they can support the propagation of electrical pulses whose spectra reaching 3 THz for a distance as long as 1 mm. As an application of these devices, also we demonstrate the THz spectroscopic characterization of liquid and powder specimens [11][12][13]. In addition, we show that even lower attenuation can be realized in quadrupole mode in threestrip CPS (TSCPS) on low permittivity substrate.…”
Section: Introductionmentioning
confidence: 96%
“…Fig. 6 is the change in the attenuation with the immersion of bovine-serum-albumin (BSA) molecules at various densities [12]. With the increase of the density, the attenuation decreases because of the capturing of the free water molecules due to the hydration of albumin molecules.…”
Section: Spectroscopy Of Liquid Specimenmentioning
confidence: 99%
“…Kitagawa et al [Kitagawa et al , 2006] demonstrated the THz spectroscopic performance of highly integrated sensor chips based on microstrip lines by measuring biomolecule/water systems. The concentration resolution of the chips reaches down to 0.05 g/ml.…”
Section: Sensorsmentioning
confidence: 99%
“…The noise figure of THz detector by photoconductive antenna is high, so that a high signal to noise ratio (SNR) is required to extract the THz signal from the signal received. Parabolic mirrors have been widely used in THz systems to focus the weak THz power to the sample to increase the SNR [1][2][3][4][5][6]. On the other hand, a bi-conical structure has been widely used as a broadband radiation device with very high field concentration at gaps between the conical structure [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Terahertz (THz) sensing technology has received considerable attention in recent years for its potential applications in the detection of biological materials, skin cancer and spectral signature for molecular vibrations in RNA, DNA strands or proteins [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%